Reflection on the Impact of Child Trafficking in Africa: A Case Study of Efia in Amma Darko’s the Housemaid - (:unkn) unknown (My University, 2024)
African women writers are committed to defend women perspectives in their writings. They have been trying to defend African women bad conditions due to their different social subjugation. This article explores the representation of child trafficking in Amma Darko’s The Housemaid, revealing its roots in poverty and cultural complicity and its devastating consequences, including psychological trauma and social marginalization. Under a textual and interpretative analysis, this work wants to use social theory as the theoretical framework. The purpose of this article is to highlight the impact of child trafficking in Africa: a case of Efia in Amma Darko’s the Housemaid. Despites the contribution of this work in literary domain by highlighting the social hindrance, this article examines a given social matter in link with trafficking human beings that the author condemns. In this novel, many little girls who have been trafficked via the channel of one of their citizens for house chores, hawking, prostitution and other hard activities.The result of this research reveals that poverty and the search for easy gain by certain parents are the principal causes of child trafficking in this novel. The study also shows that child trafficking has plenty of bitter impacts on Ghanaian societies like living in the streets, prostitution and unwanted pregnancy. The study suggests that many social beds must be interested to the matter in order to solve it definitely.
Keywords: African Research